Morin-modified carbon paste electrode as a promising tool for monitoring aluminium: An initial study - Švancara, Ivan; Kopecká, Nikol; Sýs, Milan (University of Pardubice, 2022)
This article introduces spectrophotometric and electrochemical investigations of the complex-forming reaction between morin (MO) and the aluminium ions in mild acidic media. Already in the initial stage, the latter measurements have indicated that a carbon paste electrode bulk-modified with a small portion of MO could serve as a simple voltammetric sensor for indirect monitoring the Al(III) species in selected samples, such as some pharmaceutical products.
Keywords: morin; aluminium(III); complex-forming reaction (chelation); UV-Vis spectrophotometry; voltammetry; carbon paste electrode